Penerapan Retorika Aristoteles sebagai Strategi Persuasi Pesan Layanan Masyarakat oleh Gen Alpha: Kegiatan Abdimas di SMA Fons Vitae 1 Jakarta - Putri Rindu Kinasih (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of persuasion theory is extremely important in daily life. Persuasion is crucial in situations other than marketing campaigns or political campaigns. Disseminating information to the general public and researching shifts in social norms and values both require persuasion. Aristotle's rhetorical triangle—ethos, pathos, and logos—is one of the persuasive techniques that have a significant impact on the communication industry. Aristotle's rhetorical triangle has been the subject of numerous studies, but few have addressed the problem of message delivery, particularly in digital public service announcements. The writer was encouraged to hold an ABDIMAS activity entitled